Training on the Utilization of Used Cans for Environmental Awareness for Karang Taruna - Adisurya, Susy Irma; Jasjfi, Elda Franzia; Iskandar, Layla Nurina Kartika; Puspatarini, Retna Ayu; Ariani, Ariani; Sari, Dhia Naura (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Residential areas face issues related to waste from used items, including discarded cans due to household consumption. Activities that involve direct participation are required to enhance environmental awareness among the community. This training is a tangible community service program from the Faculty of Fine Arts and Design at Universitas Trisakti, conducted for the youth of Karang Taruna Cikoko Timur RW 02, Cikoko Village, Pancoran Subdistrict, South Jakarta. The training was aimed at 10 (ten) members of Karang Taruna who were directly involved in community empowerment activities in the targeted area. The training was carried out using the PAR (Participatory Action Research) method, with direct painting training on used cans under the guidance of an instructional team. The stages of the can painting training were (1) Cleaning, (2) Coloring, and (3) Protecting. The results of this training included painted used can products created by each participant, along with learning outcomes such as (1) Understanding the characteristics of can packaging, (2) Recognizing colour composition, (3) Practicing patience and diligence, (4) Developing creativity, and (5) Raising environmental awareness by utilizing used waste found around the living area.